(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article focuses on the linguosophical problems connected with the verbal representation archetypical knowledge. Based on the lingual, philosophical, cultural and cognitive paradigms the author tends to analyze the verbal representation of archetypical concept fire.